Avaliação quantitativa da água subterrânea no estado de Mato Grosso do Sul - Silva, Caroline Aparecida de Almeida [UNESP] (Universidade Estadual Paulista (Unesp), 2012)
The use of groundwater resources in the State of Mato Grosso do Sul is expanding due to population growth, the attractive agricultural, industrial, tourism and advantages in relation to surface water resources. Groundwater can be easily found, as well as surface water, but their quality can be superior, since now many surface waters are very polluted. With increasing demand for groundwater, expand the studies about these natural resources, along with the creation of a decree and a law for the preservation and conservation of these stocks. The State of Mato Grosso do Sul is one of the richest states in Brazil's groundwater resources, being used for urban water supply in 72% of the municipalities. Hence the importance to protect and conserve these groundwater resources. The SANESUL (Basic Sanitation Company of Mato Grosso do Sul) is responsible for the uptake and distribution of groundwater in the state. This work was prepared as a contribution to the State of Mato Grosso do Sul. The database used was sought in the Information System Groundwater - SIAGAS where data were found on the existing wells in the state. The analyzes were made from the information on wells drilled in aquifers in the State of Mato Grosso do Sul, where they were checked local aquifers, flow rates, depths, drilling date, type of use and location of wells. The amount of these existing groundwater wells was also analyzed and found 1346 wells. We estimated the flow of groundwater and the second most important state results are the Serra Geral, Guarani and Bauru, which have respectively 15,554, 10,758 and 8,438 m³ / h flow exploited by summing all the wells drilled in each of these aquifers. With a population assessment of the state along with the number of existing wells, one can see that Mato Grosso do Sul is in development and that some areas need attention so that the emergency water supply remains compatible with the demand. The ...

A utilização dos recursos hídricos subterrâneos no Estado de Mato Grosso do Sul está em expansão devido ao crescimento populacional, dos atrativos agrícolas, industriais, turísticos e as vantagens em relação aos recursos hídricos superficiais. A água subterrânea pode ser facilmente encontrada, assim como a água superficial, porém sua qualidade pode ser superior, visto que atualmente muitos mananciais superficiais estão bastante contaminados. Com o aumento da demanda de águas subterrâneas, expandem-se os estudos a cerca desses recursos naturais, juntamente com a criação de decreto e uma lei para a preservação e conservação desses mananciais. O Estado de Mato Grosso do Sul é um dos estados mais ricos em recursos hídricos subterrâneos do Brasil, sendo utilizado para o abastecimento urbano em 72% dos municípios. Por isso a importância em proteger e conservar esses recursos hídricos subterrâneos. A SANESUL (Empresa de Saneamento Básico do Mato Grosso do Sul) é responsável pela captação e distribuição das águas subterrâneas no estado. Este trabalho foi elaborado como forma de contribuição para o Estado de Mato Grosso do Sul. A base de dados utilizada foi buscada no Sistema de Informações de Águas Subterrâneas - SIAGAS, onde foram encontrados dados sobre os poços existentes no estado. As análises foram feitas a partir das informações sobre os poços tubulares perfurados nos aquíferos no Estado de Mato Grosso do Sul, onde foram verificados os aquíferos locais, as vazões, as profundidades, a data de perfuração, tipo de uso e localização dos poços. A quantidade de poços existentes nesses aquíferos também foi analisada sendo encontrados 1346 poços. Estimou-se a vazão dos aquíferos e os mais importantes do estado segundo os resultados são o Serra Geral, Bauru e Guarani, os quais têm respectivamente 15.554, 10.758 e 8.438 m³/h de vazão explotada somando ...
Keywords: Aquiferos - Mato Grosso do Sul; Águas subterrâneas; Recursos hídricos - Desenvolvimento